Efficacy of Pelvic Floor Muscle Training in Women With Overactive Bladder Syndrome: A Systematic Review. Issue 7 (July 2018) - Monteiro, Silvia; Riccetto, Cassio; Araújo, Angélica; Galo, Laryssa; Brito, Nathália; Botelho, Simone
Abstract : (Abstracted from Int Urogynecol J 2018; doi: 10.1007/s00192-018-3602-x) In the adult population, the prevalence of symptoms in an overactive bladder (OAB) is approximately 17%. In women, it can reach 50%.